"Natural wine" consumers and interest in label information: An analysis of willingness to pay in a new Italian wine market segment. (1st August 2019) - Galati, Antonino; Schifani, Giorgio; Crescimanno, Maria; Migliore, Giuseppina
Abstract: Increasing public attention to issues of health and environmental sustainability has contributed to a growing consumer demand for "natural" food and drinks. As has been observed, this trend has also affected the wine market, leading to the spread of so-called "natural wine". According to the literature, consumers who are aware of the social and environmental impact of their consumption choices pay more attention to the information displayed on the label as a tool to reduce the risk associated with their purchase. This study seeks to identify which consumers are willing to pay for natural wine and to understand what information on the label influences their choice. This study is one of the first in wine research to analyse consumers of the "natural" wine recently appearing on the market to satisfy the need of health and environmentally conscious consumers. The findings indicate that consumers are willing to pay a premium price for "natural" wine, and this choice is positively affected by the importance attributed to information on the ingredient content, production method and sensory characteristics included on the wine label. Millennial consumers are also more likely to pay a high premium price for "natural" wine. Highlights: Conscious consumers pay more attention to information displayed on the label. WTP was used to understand consumers preferences for natural wine. Multiple price list approach was adopted to elicit consumers' WTP for natural wine. Information displayed on the label positively affect consumers' WTP for natural wine.